Analisis Pengaruh LDR, NPL, DAN NIM Terhadap ROA Pada Bank Di Indonesia - Zakirah, Raniah Hasna; Hasanuh, Nanu (Tirtayasa Ekonomika, 2024)
The purpose of this study is to ascertain how LDR, NPL, and NIM affect ROA banking organizations that are registered with the Financial Services Authority (OJK) for the years 2018-2022. Methods of analysis. This study employs a quantitative analysis methodology. The multiple linear regression analysis and the classical assumption test are the research data analysis tools. Financial reports from banks registered with the Financial Services Authority (OJK) for the years 2018–2022 were used to gather research data. The conclusion that can be drawn is that LDR has a positive effect on ROA of banking companies in the 2018-2022 period. Then, NPL has a positive effect on ROA of banking companies for the 2018-2022. Then, NIM has a positive effect on the company's ROA banking in the 2018-2022 period. And, LDR, NPL and NIM jointly influence the ROA of banking companies in the 2018-2022 period.